2020
DOI: 10.3390/ijerph17207370
|View full text |Cite
|
Sign up to set email alerts
|

Communication Support Needs in Adults with Intellectual Disabilities and Its Relation to Quality of Life

Abstract: Research suggests that individuals with intellectual disabilities (ID) experience difficulties in communication, ranging from intelligibility issues to more severe problems in the use and comprehension of spoken, written or sign language. Despite the negative effects that the inability to communicate have on quality of life (QoL), not much research has explored the relationship between communicative competence and QoL in the adult population with ID. The aim of this study was to describe the global communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Communication difficulties (CD) are prevalent among individuals with IDD; an estimated 57.9% of those with intellectual disabilities (ID) and 40% of those with ASD struggle with communication ( Autism Statistics and Facts , n.d. ; García et al, 2020 ). These difficulties involve challenges in sending, receiving, processing, and/or comprehending abstract ideas, verbal and nonverbal communication, and/or graphic symbol systems and range from mild to profoundly severe (Definitions of Communication Disorders & Variations, 1993 ).…”
mentioning
confidence: 99%
“…Communication difficulties (CD) are prevalent among individuals with IDD; an estimated 57.9% of those with intellectual disabilities (ID) and 40% of those with ASD struggle with communication ( Autism Statistics and Facts , n.d. ; García et al, 2020 ). These difficulties involve challenges in sending, receiving, processing, and/or comprehending abstract ideas, verbal and nonverbal communication, and/or graphic symbol systems and range from mild to profoundly severe (Definitions of Communication Disorders & Variations, 1993 ).…”
mentioning
confidence: 99%
“…These findings underscore how severe early childhood language deprivation impacts communication skills [ 10 ], even in our population where great effort has been taken to optimize access to communication through sign language in adult life. Other research in individuals with intellectual disabilities could show a strong association between communicative competences and QOL [ 37 ], which highlights the importance of access to language and communication. In contrast to the findings of Sparrow et al 2005, in the present study with a sample who is prelingually deaf with mild cognitive deficits, the socialization domain appeared to be the weakest [ 15 ].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have confirmed the importance of communication around the health of people with intellectual disability and suggest training professionals. These topics are also reflected on in literature; several studies have suggested teaching communication skills to support workers to improve health information exchange [ 59 , 65 67 ], and other studies have suggested training for health professionals on communication with people with intellectual disability specifically [ 68 70 ]. Therefore, care provider organisations can facilitate communication training and make training tools accessible for their staff [ 71 ].…”
Section: Discussionmentioning
confidence: 99%